Nory Ryan's song - Giff, Patricia Reilly (New York : Scholastic, 2001)
When a terrible blight attacks Ireland's potato crop in 1845, twelve-year-old Nory Ryan's courage and ingenuity help her family and neighbors survive.
Originally published: New York : Random House, c2000.
"This edition is only available for distribution through the school market"--P.[4] of cover.
Keywords: Famines -- Ireland -- Fiction; Brothers and sisters -- Fiction; Survival -- Fiction; Ireland -- History -- Famine, 1845-1852 -- Juvenile fiction; Ireland -- History -- Famine, 1845-1852 -- Fiction; Ireland -- Emigration and immigration -- Fiction